Anti-N-Methyl-D-Aspartate Receptor Antibody Mediated Neurologic Relapse Post Herpes Simplex Encephalitis: A Case Series. Issue 8 (August 2016) - Geoghegan, Sarah; Walsh, Aoibhinn; King, Mary D.; Lynch, Bryan; Webb, David; Twomey, Eilish; Ronan Leahy, T.; Butler, Karina; Gavin, Patrick
Abstract : Despite the advent of antiviral therapy, herpes simplex encephalitis (HSE) remains a devastating condition with significant morbidity and mortality. Neurologic relapse after initial improvement is generally attributed to herpes simplex virus reactivation. In 2013, inflammation caused by anti- N -methyl-D-aspartate receptor antibodies was reported in association with cases of neurologic relapse after herpes simplex encephalitis. We present 3 such cases and discuss diagnostic and management dilemmas. Abstract : Supplemental Digital Content is available in the text.